CD1d-Restricted Natural Killer T Cells Are Preserved in Indian Long-Term Nonprogressors. (1st August 2017) - Singh, Dharmendra; Ghate, Manisha; Godbole, Sheela; Kulkarni, Smita; Thakar, Madhuri
Abstract : Background: Natural killer T (NKT) cells act as a bridge between innate and adaptive immune responses. Limited information is available regarding the role of NKT cells in the HIV disease progression especially HIV-1 C infection. Methodology: NKT cells were characterized for their frequency and the activation, aging, exhaustion status, and their proliferation ability in 32 long-term nonprogressors (LTNPs), 40 progressors, 18 patients before and after suppressive combination antiretroviral therapy (cART) along with 35 HIV-1–negative subjects using multicolor flow cytometry. Results: The frequencies of total NKT cells and their subpopulation were significantly higher in LTNPs as compared with those obtained in progressors ( P < 0.0001) and were significantly associated with higher CD4 counts and with lower plasma viral loads. The percentage of activated, aged, and exhausted NKT cells were significantly lower in LTNPs as compared with the progressors and inversely correlated with CD4 count and positively with plasma viral loads. The NKT cells from the LTNPs showed higher proliferation ability. The frequency and proliferation ability of the NKT cells were partially restored after 12 months of suppressive cART but still lower than the levels in LTNPs. The degree of restoration after cART was similar in both CD4 + and CD4 − NKT cells. Conclusion: The findings demonstrate significant association of preserved NKT cells with the nonprogressive HIV infection and also showed that exhausted NKT cells are associated with disease progression. Further characterization of their functionality and assessment of sustenance in HIV infection will help to understand the HIV pathogenesis and to develop immune therapies. Abstract : Supplemental Digital Content is Available in the Text.